Trans fatty acid intake among the population of the city of São Paulo, Brazil Consumo de ácidos grasos trans en la población de la ciudad de Sao Paulo, Sureste de Brasil Consumo de ácidos graxos trans na população da cidade de São Paulo, Brasil - Michelle Alessandra de Castro; Rodrigo Ribeiro Barros; Milena Baptista Bueno; Chester Luiz Galvão César; Regina Mara Fisberg (Universidade de São Paulo, 2009)
OBJECTIVE: To analyze the monounsaturated and polyunsaturated trans fatty acid intake among the general population. METHODS: A cross-sectional study was conducted in São Paulo, Southeastern Brazil, in 2003, on a representative sample of 2,298 male and female subjects, including 803 adolescents (12 to 19 years), 713 adults (20 to 59 years) and 782 elderly people (60 years or over). Food intake was measured using 24-hour recall. Mean trans fatty acid intake was described according to gender and age group. RESULTS: The mean trans fatty acid intake was 5.0 g/day (SE = 0.1), accounting for 2.4% (SE = 0.1) of total energy and 6.8% (SE = 0.1) of total lipids. The adolescents had the highest mean intake levels (7.4 g/day; 2.9% of energy) while the adults and the elderly had similar intake (2.2% of energy for both; 6.4% of lipids and 6.5% of lipids, respectively). The mean trans fatty acid intake among adult and elderly women (approximately 2.5% of energy and 7.0% of lipids) was higher than among men in the same age group. The food item with the highest contribution towards trans fatty acids was margarine, accounting for more than 30% of total intake, followed by filled cookies among adolescents and meat among adults and the elderly. CONCLUSIONS: The trans fatty acid intake is above the level recommended by the World Health Organization. Replacement of the trans fatty acids in manufactured food items may be an effective measure for reducing trans fatty acid intake in Brazil. OBJETIVO: Analizar el consumo de ácidos grasos moninsaturados y polinsaturados de configuración trans en la población general. MÉTODOS: Estudio transversal realizado en Sao Paulo, Sureste de Brasil, 2003, con muestra representativa de 2.298 individuos, siendo 803 adolescentes (12 a 19 años), 713 adultos (20 a 59 años) y 782 ancianos (60 años o más), de ambos sexos. El consumo alimentario fue medido por medio del recordatorio alimentario de 24 horas. Los valores promedios de ingestión de ácidos grasos trans fueron descrito según sexo y grupo etario. RESULTADOS: El consumo promedio de ácidos grasos trans fue de 5,0 g/día (EP=0,1), correspondiendo a 2,4% (EP=0,1) del total calórico y 6,8% (EP=0,1) del total de lípidos. Los adolescentes presentaron los mayores promedios de ingestión (7,4g/día y 2,9% energía), mientras que los adultos y ancianos registraron ingestión semejante (2,2% energía; 6,4% lípidos y 6,5% lípidos, respectivamente). Los promedios de consumo de ácidos grasos trans entre mujeres adultas y ancianas (aproximadamente 2,5% energía y 7,0% lípidos) fueron mayores que los promedios de los hombres del mismo grupo etario. El alimento de mayor contribución para el consumo de ácidos grasos trans fue la margarina, representando más de 30% del total ingerido, seguido de la galleta rellena para los adolescentes y de la carne bovina para los adultos y ancianos. CONCLUSIONES: El consumo de ácidos grasos trans se encuentra por encima del preestablecido por la Organización Mundial de la Salud. La sustitución de los ácidos grasos trans de los alimentos industrializados puede ser una medida eficaz para la reducción del consumo de este tipo de grasa en Brasil. OBJETIVO: Analisar o consumo de ácidos graxos monoinsaturados e poliinsaturados de configuração trans na população geral. MÉTODOS: Estudo transversal realizado em São Paulo, SP, 2003, com amostra representativa de 2.298 indivíduos, sendo 803 adolescentes (12 a 19 anos), 713 adultos (20 a 59 anos) e 782 idosos (60 anos ou mais), de ambos os sexos. O consumo alimentar foi medido por meio do recordatório alimentar de 24 horas. Os valores médios de ingestão de ácidos graxos trans foram descritos segundo sexo e faixa etária. RESULTADOS: O consumo médio de ácidos graxos trans foi de 5,0g/dia (EP=0,1), correspondendo a 2,4% (EP=0,1) do total calórico e 6,8% (EP=0,1) do total de lipídios. Os adolescentes apresentaram as maiores médias de ingestão (7,4g/dia e 2,9% energia), enquanto os adultos e idosos registraram ingestão semelhante (2,2% energia; 6,4% lipídios e 6,5% lipídios, respectivamente). As médias de consumo de ácidos graxos trans entre mulheres adultas e idosas (aproximadamente 2,5% energia e 7,0% lipídios) foram maiores que as médias dos homens de mesma faixa etária. O alimento de maior contribuição para o consumo de ácidos graxos trans foi a margarina, representando mais de 30% do total ingerido, seguido do biscoito recheado para os adolescentes e da carne bovina para os adultos e idosos. CONCLUSÕES: O consumo de ácidos graxos trans encontra-se acima do preconizado pela Organização Mundial da Saúde. A substituição dos ácidos graxos trans dos alimentos industrializados pode ser uma medida eficaz para a redução do consumo desse tipo de gordura no Brasil.